Operational Risk and Profitability of Indonesian Islamic Banks: Examining the Mediating Role of Financial Intermediation - Hepy Octalia Elfa Kolina; Agus Sukoco (Indonesia Academia Research Society, 2025)
The rapid growth of Islamic banking in Indonesia has increased the importance of understanding the factors that influence bank profitability and financial sustainability. Despite significant expansion in assets, financing, and third-party funding, Islamic banks continue to face challenges in operational efficiency, financing risk, and liquidity management. This study aims to examine the influence of operational efficiency and financing risk on the profitability of Islamic commercial banks in Indonesia, with financial intermediation acting as a mediating variable. Specifically, the research analyzes the effects of Operating Expenses to Operating Income (BOPO) and Non-Performing Financing (NPF) on profitability measured by Return on Assets (ROA), while Financing to Deposit Ratio (FDR) is tested as an intervening variable. The study adopts a quantitative explanatory research design, using secondary data from the annual financial statements of Islamic commercial banks registered with the Financial Services Authority (OJK) for the 2014–2024 period. The data are analyzed using the Structural Equation Model (SEM) to evaluate both direct and indirect relationships among variables. The results show that BOPO has a negative and significant effect on ROA, indicating that operational inefficiency reduces bank profitability. FDR has a positive and significant effect on profitability, confirming the important role of financial intermediation in improving bank performance. In contrast, NPF does not directly affect profitability but does significantly affect financial intermediation. The mediation analysis reveals that FDR does not mediate the relationship between BOPO and ROA but significantly mediates the relationship between NPF and ROA. These findings highlight the critical importance of operational efficiency and effective financing distribution in improving Islamic bank profitability, while also emphasizing the indirect role of financing risk through the financial intermediation mechanism.